Integrasi Hukum Islam dalam Sistem Pluralisme Hukum Papua: Telaah Normatif terhadap Peraturan Daerah: Integration of Islamic Law in Papua’s Legal Pluralism System: A Normative Review of Regional Regulations - Ansar, Lukman; Makkarateng, Ma'adul Yaqien; Tarmizi, Tarmizi; Mustafa, Mustafa; Sari, Dewi Arnita (ISTIDLAL, 2025)
This article aims to analyze the integration of Islamic law into the legal pluralism system in Papua through a normative study of various Regional Regulations containing Islamic legal norms. The study focuses on how Islamic law negotiates with Papuan customary law and state law in the context of a highly multicultural society. This research uses qualitative methods with a normative approach through analysis of legislation and legal pluralism theory. The research findings show that the integration of Islamic law in Papua is not uniform, but rather a mosaic of diverse norms and practices, reflecting the social character of the community. Specific applicability models, such as the requirement for Muslim students to read and write the Quran in Fakfak, provide space for the expression of religious identity while maintaining social sensitivity. Conversely, inclusive models, such as the regulation of zakat and mosque management in South Sorong, demonstrate a more adaptive strategy to diversity. In certain cases, such as inheritance disputes, communities choose hybrid mechanisms that combine sharia and customary principles to maintain harmony. The success of integrating Islamic law into the Papuan legal system is largely determined by policy sensitivity to diversity, the involvement of local leaders, and the flexibility of legal norms.